2017
DOI: 10.22159/ijap.2017v9i2.16345
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Different Variables on the Formulation of Mucoadhesive Buccal Patches of Captopril

Abstract: Objective: The objective of this research was to formulate the captopril as mucoadhesive buccal films for hypertension treatment and studying the effect of different variables on the physical and mechanical behavior of the prepared films. Methods:The bucco-adhesive patches were prepared using hydroxyl propyl methyl cellulose K4 (HPMC) as film forming a polymer with secondary polymer included carbopol 934 and eudragit RL100. The patches were prepared by a solvent casting method and evaluated for the weight vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…The percentage drug content of all formulations was found to be in the range of 97-99 %. Among the formulations prepared, it was observed that FC takes longer time to disintegrate since it contains Carbopol 934 and HPMC which is highly viscous at increased concentration [16,17]. The results for all formulations and the average of 3 determinations are given in table 2.…”
Section: Physico-chemical Evaluation Of Prepared Buccal Patchesmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage drug content of all formulations was found to be in the range of 97-99 %. Among the formulations prepared, it was observed that FC takes longer time to disintegrate since it contains Carbopol 934 and HPMC which is highly viscous at increased concentration [16,17]. The results for all formulations and the average of 3 determinations are given in table 2.…”
Section: Physico-chemical Evaluation Of Prepared Buccal Patchesmentioning
confidence: 99%
“…Hence the formulation provides sustained release of drug. The poor solubility of SA limits the swelling of the patch [17] ( fig. 2).…”
Section: Measurement Of Swelling Indexmentioning
confidence: 99%
“…Blank matrices were composed of different concentrations of PVA and PVP (table 1) which were prepared by a plate casting method [4,15]. PVA was weighted and dissolved in boiled water, while PVP was weighted and dissolved in hot water to yield solutions at 12 % w/w.…”
Section: Preparation Of Blank and Lidocaine Hcl Matricesmentioning
confidence: 99%
“…Materials with hydrophobicity, low water permeability and drug impermeability properties such as melted wax [10], ethyl cellulose [1,4,11], and Eudragit RL100 [12] have been used as a backing membrane. A wide range of polymers such as hydroxypropyl methylcellulose, carbopol, poly (vinyl alcohol) (PVA), and poly (vinyl pyrrolidone) (PVP) [13][14][15][16][17] have been employed as a matrix and mucoadhesive layer in buccal patches. In order to improve the film properties, including film-forming ability, mechanical and mucoadhesive properties, a combination of hydrophilic polymers is generally used.…”
Section: Introductionmentioning
confidence: 99%
“…Upon removal of patches, the resulting reaction was evaluated according to US-FDA grading scale. [17][18][19][20].…”
Section: Primary Skin Irritation Studiesmentioning
confidence: 99%